Pemanfaatan Mini Vlog sebagai Media Observasi Pembelajaran Anak Usia Dini di TK An Nida - Hilda Zahra Lubis; Maldina Aulia Rahmi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Early childhood education emphasizes meaningful learning experiences through play and social interaction. The development of digital technology has encouraged innovations in learning, one of which is the use of mini vlogs as a medium for documenting and evaluating learning activities in kindergarten. This study aims to describe the implementation of early childhood education through mini vlogs at An Nida Kindergarten and to examine teacher-child interactions, the learning atmosphere, and problems that arise during activities. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through indirect observation of mini vlog learning videos and supporting documentation. The results show that learning at An Nida Kindergarten is interactive, enjoyable, and appropriate for early childhood characteristics, although there are obstacles such as differences in children’s abilities, limitations in learning media, and uneven parental support. In conclusion, mini vlogs are effective as a medium for documentation, learning evaluation, and a means of communication between teachers and parents in supporting the quality of early childhood education.